Reasoning decline during aging under familiar and unfamiliar physics - Dexter, Melissa; Grandchamp des Raux, Hélène; Ossmy, Ori (Frontiers in Aging, 2025)
Physical reasoning is the capacity to anticipate how an environment will change as its elements move and interact. This cognitive skill, which is based on humans’ intuitive knowledge of physics, underlies everyday tasks that are potentially critical to older adults, such as avoiding collisions. Nevertheless, the effects of aging on physical reasoning remain understudied. Here, we tested physical reasoning among younger (18–35 years) and older (over 65 years) adults as they completed different difficulty levels of a physical reasoning paradigm. Participants viewed object displacements in a virtual environment and had to decide the outcome of that displacement under different gravity forces (terrestrial gravity, half, and double terrestrial gravity). We also tested distinct physical action concepts—supporting, launching, and clearing—because those index different demands on object-interaction complexity and are known to differ during child development. This allowed us to determine whether age-related differences reflect a global decline in physical reasoning or a selective difficulty with conceptually more complex, multi-object predictions. Our results revealed that older adults performed comparably to younger adults in straightforward fail conditions but exhibited lower accuracy in more complex scenarios, implicating subtle object interactions and predicting successful outcomes. This decline did not intensify under altered gravity, suggesting that the ability to recalibrate to new physical contexts may not be selectively affected by aging. However, older adults were disproportionately challenged by tasks featuring action concepts involving more complex object interactions, indicating that higher complexity burdens physical reasoning in later life. These findings highlight how intuitive physics can still degrade in key aspects of precision and complexity. Understanding these shifts is important for developing supportive strategies that help maintain functional independence in older adulthood, particularly in tasks requiring challenging physical reasoning.